Pengaruh Prinsip-Prinsip Good Corporate Governance Pada Kinerja Keuangan Lembaga Perkreditan Desa ( LPD ) Di Kecamatan Penebel - I Made Gede Moniarta Jaya; Ni Putu Trisna Windika Pratiwi (UNHI Press, 2023)
The research to discover the principles of good corporate governance on the financial overallperformance of village credit score establishment ( LPD ) in Penebel Subdistrict.The population in this studi was in 20 LPD in Penebel Districts, Tabanan Regency with a sample number of 40 respondents. Sample determination methods by purposive sampling, data analysis techniques used are descriptive statistics, validity testss, reliability testss, classicall asssumption testss, multipple linear regressions analyssis, determination coefficients (R2), F tests, t tests. The resultted of this study showed thats: Transpareency variable, Accountaability variable Indepndence variable ,Fairneess variable and have a possitive and significantt effect on the the Villlage Creditt Institutionn (LPD) in Penebel District Financial Performance and Respnsibilityvariable has an insignificant negative effect Financial Performance on the Village Credit Institution (LPD) in Penebel District